THE EFFECT OF SERVICE COMPENSATION, MOTIVATION, AND DISCIPLINE ON WORK PRODUCTIVITY AND ITS IMPLICATIONS ON SERVICE QUALITY (Study at Malingping Regional Hospital, Banten Province) - Yusup Erisyadi; Farida Yuliaty; Kosasih; Assoc. Prof. Dr. Dr. H. Sumeidi Kadarisman, S.E., M.M; Prof. Dr. VIP Paramarta; Drs., M.M5, Fittiana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Improving the quality of hospital services is greatly influenced by employee productivity. Human resource management factors such as compensation for services, work motivation, and work discipline are crucial elements that can influence productivity and the quality of healthcare services provided to the public. This study aims to analyze the influence of service compensation, motivation, and discipline on work productivity and their implications for service quality at Malingping Regional General Hospital, Banten Province. The study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to 193 hospital employee respondents. Data analysis was performed using path analysis with the help of SPSS version 26. The results of the study indicate that motivation and discipline have a positive and significant effect on employee work productivity, while service compensation does not have a significant partial effect on work productivity. Simultaneously, compensation, motivation, and discipline have a significant effect on work productivity. Furthermore, work productivity has a significant effect on service quality. The coefficient of determination indicates that the variables of compensation, motivation, discipline, and productivity are able to explain 94.1% of the variation in service quality. The results of this study indicate the importance of strengthening employee work motivation and discipline policies to improve the quality of hospital services.